GC-MS analysis of rhizome ethanol extracts from Curcuma aeruginosa accessions and their efficiency activities as anticancer agent - Waras Nurcholis; NURUL KHUMAIDA; MARIA BINTANG; MUHAMAD SYUKUR (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Nurcholis W, Khumaida N, Bintang M, Syukur M. 2021. GC-MS analysis of rhizome ethanol extracts from Curcuma aeruginosa accessions and their efficiency activities as anticancer agent. Biodiversitas 22: 1179-1186. This work aimed to evaluate the bioactive compounds and anticancer activity in rhizome extract of ten Curcuma aeruginosa accessions to explore their pharmacological values. The GC-MS analysis was used to identify bioactive compounds. The cytotoxic activity was performed against MCF-7 (Human breastadeno carcinoma) and Vero cell lines using MTT assay. The GC-MS analysis revealed 71 of the compounds as sesquiterpenes (36), monoterpenes (20), phenolics (5), diterpenes (4), phenanthrene (1), tetrapeptides (1), oxazole (1), triazine (1), piperidine (1), and oxygenated hydrocarbons (1). The isocurcumenol was the most dominant metabolite in ethanol extract of C. aeruginosa rhizome, with the highest produced by KP accession (22.01%) followed MD accession (21.12%). However, camphor and ?-elemene were the metabolites produced by all accessions studied. In the Vero cell line as a normal cell, the cytotoxic activity varied from 13.28% (MD) to 45.17% (PW). Furthermore, the cytotoxic activity ranged from 1.16% (LC) to 49.70% (MD) against the MCF-7 cell line. The highest anticancer activity was produced in MD accessions; thus, it can be used as a source of quality raw materials for the pharmaceutical and food industry. Besides that, it can also be further developed to obtain superior varieties through plant breeding programs.